Turismo alternativo para el desarrollo del distrito de Santa Cruz de Flores- provincia de Cañete-Lima 2019 - Arias Espichán, Manuel Godofredo (2023)
The present work has considered a diagnosis of the reality of tourism in the District of Santa Cruz to propose it as an alternative for local development given the natural and archaeological conditions it possesses, finding that the district has deficiencies in relation to various factors consistent with this situation. that can be overcome such as the improvement of the tourist offer in relation to the tourist plant such as transport, hotel infrastructure and restaurants that is scarce and deficient and on the other hand propose to the Municipality the importance of tourism for the sustainable development of the district. The method adheres to a procedure that includes three phases, namely: the collection of documentary and theoretical information, the collection of data in the field and finally the analysis, evaluation in accordance with the problems and objectives set. The results of the investigation determine that the current load capacity does not satisfy the tourist, because there is a deficit for the lodging of the tourists, there is also a lack of transport and adequate restaurants and on the other hand there is an interest of the local authority to develop tourism. as an alternative source of local development.